The Book of Crypto The Complete Guide to Understanding Bitcoin, Cryptocurrencies and Digital Assets - Arslanian, Henri (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XXXIII, 458 p. 121 illus., 118 illus. in color.